PENGEMBANGAN MEDIA PEMBELAJARAN TANGGA PINTAR UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PADA MATA PELAJARAN MATEMATIKA SEKOLAH DASAR - Ratumbuysang, Monry Fraick Nicky Gillian; Salim, Agus; Mastur, Mastur; Raudah, Raudah (Universitas Bhinneka PGRI, 2023)
This study aims to produce a product in the form of smart ladder learning media. Moreover, this is to know the feasibility and the effect of smart ladder learning media on students' numeracy abilities. This type of research is Research and Development (RD) using the Four-D (4D) development model. The development stages include: the define, the design, the development, and the disseminate stage. Data collection techniques in the form of observation, interview, questionnaire, and test. The feasibility test involved four experts consisting of instrument, material, media, and learning experts. The data analysis technique used is descriptive quantitative. The results of the study show that smart ladder learning media is appropriate to use based on the results of the assessment of material experts obtaining score 94.54%, media experts 96.25%, and learning experts 90.90%. The results of improving the numeracy skills of students grade 1 obtained an N-gain value of 0.97 and students grade 2 obtained an N-gain value of 0.91, which the two N-gain values were included in the